2020
DOI: 10.1111/jcmm.15726
|View full text |Cite
|
Sign up to set email alerts
|

Rab27A promotes cellular apoptosis and ROS production by regulating the miRNA‐124‐3p/STAT3/RelA signalling pathway in ulcerative colitis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Among them, 339 unique proteins existed in the former, while 243 proteins uniquely existed in the latter ( Fig. 7 B and Table 1 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 339 unique proteins existed in the former, while 243 proteins uniquely existed in the latter ( Fig. 7 B and Table 1 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“… 26 In multifactorial inflammatory diseases, such as ulcerative colitis, miR‐124‐3p might also regulate cellular apoptosis and reactive oxygen species production. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB pathways, including the RELA-dependent canonical pathway and the RELB-dependent noncanonical pathway, are essential for immune response modulation ( Hoesel and Schmid, 2013 ). Studies at UC also found that cellular apoptosis and ROS production could also be regulated by the RELA-related signal pathway ( Luo et al, 2020 ). In addition, phosphorylation and acetylation of RELA contribute to the transcriptional activation of various inflammatory and catabolic genes ( Kleppe et al, 2018 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%